INTERNATIONAL EXPERIENCE IN COUNTERING TERRORISM - А. Baisseitova; О. Smailov (Хабаршы. Заң сериясы, 2020)
The article deals with issues relating to international cooperation in countering terrorism and using the positive experience of foreign countries in ensuring security. Terrorism and extremism are estimated by the authors as the main threats not only to national but also to international security. Recognizing the global nature of these threats, the international community seeks to develop a common policy of struggle, since the effectiveness of anti-terrorism measures can only be achieved with active interstate cooperation. Currently, at the level of the United Nations, a number of conventions and protocols have been adopted, aimed at unifying legal concepts in the sphere of countering terrorism and extremism, creating unified mechanisms for preventing and suppressing crimes of a terrorist nature. The paper analyzes the main provisions of these international conventions and evaluates their importance for ensuring security throughout the world. Considering that the Republic of Kazakhstan has not so great practical experience in countering terrorism, the issues of researching legislation and practice of the law enforcement agencies of foreign countries that have been fighting for many years against terrorism and extremism are of particular relevance. The authors, analyzing the modern legal framework and the practice of joint activities of the competent authorities of various states in countering terrorism, justify their proposals for the further development of international cooperation in this field. The study of foreign experience, its systematization, adaptation to the conditions of Kazakhstan will help optimize the activities against terrorism and extremism and avoid possible mistakes in the choice of means and methods of such a struggle.